Learning to change : the experience of transforming education in South East Europe - Bassler, Terrice (Central European University Press, 2005)
"This collection of first-person narratives by specialists in education from South East Europe makes vivid the politics and paradoxes of the transformation of education systems. The book chronicles the profound effect on schooling caused by the armed conflict, post-communist transition, and increasing openness of the last fifteen years. The stories narrate the thoughts and feelings of individuals, experienced first-hand, in the classrooms of eleven countries and territories."--Jacket